America the beautiful : rediscovering what made this nation great - Carson, Ben. (Zondervan, 2012)
Tackling the issues at the forefront of the American mind--healthcare, education, capitalism, and more America the Beautiful is indispensable reading. From four-time bestselling author, internationally renowned neurosurgeon, and humanitarian Dr. Ben Carson, here is a sobering and inspiring manifesto of America's greatness, her failings, and the values and changes it will take to carry our country into a brilliant and prosperous future.